Caracterização e análise da região codificadora do gene fruitless em moscas-das-frutas (Anastrepha obliqua) - Szrajer, Marcos Rosolino (2011)
The fruit flies (Anastrepha sp) are organisms endemic to the Neotropics that are similar morphologically but present some behavioral, reproductive and molecular variations. Among these insects we can highlight the fraterculus group, which consists of a set of cryptic species, between them Anastrepha oblique, that represents threats to national fruit culture. The effective control of this grouping requires the expansion of the few studies concerning to the biology and history of populations which has a very complex systematic. Previous works suggest a high rate of evolution of genes related to reproductive issues and recognition of partners due to the high selective pressures involved in that relationship, hence, we chose to work with the fruitless gene which is recognized for its role in sexual differentiation and male courtship behavior in dipteran insects. Since a small region of this gene was already been amplified in our laboratory, we amplified and described the flanking sequences by RACE-PCR technique which used primers constructed targeting the 5 'and 3' ends. We used cDNA libraries produced from the extraction of mRNAs from different stages of development of these organisms enabling the identification of different isoforms arising from alternative splicing and structural characterization of the coding region (CDS) common to both sexes. We compared the data generated with the corresponding sequences of the fruitless gene in other insect species identifying the rate of similarity for nucleotides and amino acids (identity ratio) which revealed that the éxons coding for specific domains such as BTB and Zinc Fingers tend to remain more conserved in relation to other regions and éxons from Connector Region. Subsequently, we performed positive selection tests through the Relaxed Branch-site test and Strict Branch-site test, which were contrasted by Likelihood Ratio Tests (LRT) which identified 25 new sites evolving under positive selection, corroborating the findings of Sobrinho e de Brito (2010) and suggesting the presence of these forces on specific regions of this important gene linked to reproductive aspects of several major groups of insects.